A comparison of non-traditional online and traditional wet-lab experiences in human anatomy and physiology: An innovative approach for pre-licensure nursing education. (December 2021) - Massey, Ann; Zhang, Weihua; Amar, Angela
Abstract: Background: The contributions of student laboratory experiences to student learning in pre-licensure science classes are not well understood. Despite the generally accepted premise that traditional hands-on laboratory experiences are essential to knowledge construction and superior to non-traditional online experiences, the literature suggests that both experiences promote equal levels of student learning. Objectives: We compared academic performance of students enrolled in a Human Anatomy and Physiology II course with hands-on laboratory to that of students enrolled in the same course but with online laboratory by examining several measures of student learning. Design and participants: This was a quasi-experimental study of undergraduate students aged 18–22 years enrolled in equivalent human anatomy and physiology courses on two separate campuses of a private research university in the United States. One course was associated with hands-on laboratory while the other course was associated with online laboratory. Methods: The Human Anatomy and Physiology Society standardized exam was administered as a pre-test/post-test assessment at the beginning and end of the academic year. Lecture exam scores, laboratory exam scores, and overall course grades served as measures of student learning. Comparisons of student performance between hands-on and online laboratory groups were made using t -tests. Results: Student performance on the pre-test and overall course grades from Human Anatomy and Physiology (part I) were not different between groups. While students in the online lab group did earn significantly higher Human Anatomy and Physiology (part II) course grades, their performance on lecture exams, laboratory exams, and the post-test assessment was not different. Conclusions: Students in a pre-licensure prerequisite course with online laboratory demonstrated mastery of basic science concepts equal to or better than students in the same course with traditional hands-on laboratory. Online laboratory experiences may represent an appropriate, accessible and cost-effective teaching modality for pre-licensure coursework.